FAKTORPENYEBAB PESERTA DIDIK MELAKUKAN PERILAKU MENYONTEK DALAM UJIAN (Studi di MTs S Sikabau Dharmasraya) - Wilda, Erlina; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
From this research, the researcher found the phenomenon that happened in the class, that is the students cheating in the examination class. From the phenomenon above, the researcher discuss about: what factors that make the students cheating in the examination (a study at MTs S SikabauDharmasraya). This research described about the internal and external factors that make students cheating in the examination class. The method of this research is a descriptive research. The population of this research was all of students at MTs S Sikabau Dharmasraya in academic year 2013/2014, the total students are 150 students. To take the sample in this research, the researcher used stratified random sampling. So, the total sample are 61 students. The instrument of this research was angket, and to analyse the data the researcher used percentage technique.Keywords: cheating, students,internal, external